OUTCOME OF PRECONTOURED ANATOMICAL PLATE IN INTRAARTICULAR FRACTURES OF PROXIMAL TIBIA (The Research of Medical Science Review, 2025)
Intraarticular fractures involving the proximal tibia can be particularly difficult to manage because of the mechanical importance of the tibial plateau, and the anatomic challenge posed by this region of the knee. This cross- sectional study was done at Allama Iqbal Teaching Hospital to compare the results of the treatment of intraarticular comminuted fractures of the proximal tibia using precontoured anatomical locking compression plates (LCP). This enrollment involved 124 patients who satisfied the Schatzker’s classification type V and VI fractures in this prospective study. Operative treatment was performed through an anterolateral approach with open reduction and internal fixation with anatomical precontoured LCPs with standard protocol rehabilitation post-operatively. Over the period of six months patients were observed for various sign, which included infection rates, signs of bony union, postoperative ROM as well as the degree of weight bearing allowed. The study findings showed that every patient achieved union with a mean time to union of 14 weeks. Superficial infections ranged at about 5%, and all the infected patients were successfully treated using antibiotics. All deep infections were not reported. Active joint flexion (0 to 130) was regained in 98% of the patients at the end of the follow-up period. Partial weight-bearing was started at 12 Weeks and became full from 16 Weeks in most of the patients. For, the study reveals that precontoured anatomical LCPs provide effective and stable internal fixation, good union; low infection complication, and favorable functional result in the management of the OTA-A3 type of complex intra-articular proximal tibial fractures. From these findings anatomical plating is recommended as the standard of care for such fractures because of better patient outcomes and reduction in immediate and long-term morbidities.